Non linearity of the ball/rubber impact in table tennis: experiments and modeling - Rinaldi, R. G.; Manin, L.; Bonnard, C.; Drillon, A.; Lourenco, H.; Havard, N. (Procedia Engineering, 2016)
Along with comfort, the speed is a key metric used to qualify the performance of a table tennis racket. The restitution coefficient which corresponds to the ratio between the velocities of the ball right before and after normally impacting the racket relates to the speed performance: the higher the restitution coefficient, the greater the speed. Thus, understanding the normal impact problem is key and suggests investigating the effects of the intrinsic properties and architectures of the constituents of the racket. In this work, both experimental and numerical studies were pursued. Experimentally, normal impact tests were performed for varying launching velocities on samples made of isolated or associated constituents of a table tennis racket and the restitution coefficients calculated. Numerically, 3D finite elements simulations were conducted to replicate the normal impact conditions while incorporating the time-dependent constitutive behavior of the polymeric elements contributing during the impact: the racket constituents (the foam and the compact) and the ball. The restitution coefficients are seen to decrease with increasing launching velocity, while being minimum when the two racket polymeric constituents are associated. A fair agreement is obtained with the FE simulations in which the sample/ball contact zone is identified as a ring with its mean radius increasing till the maximum crushing. Ultimately, additional FE calculations confirm that the friction plays a key role in the energy dissipation process, alongside with the rate-dependent behavior and architecture of the polymeric constituents.